2017
DOI: 10.1111/pai.12715
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic esophagitis phenotypes: Ready for prime time?

Abstract: Eosinophilic Oesophagitis (EoE) is one of the most common causes of reflux like symptoms and feeding problems in children and food impaction and dysphagia in adults with a prevalence of 1:2500. Therapeutic options include diet, use of swallowed corticosteroids or dilation. In the last several years, recent clinical and translational research have identified some common and distinctive features, for example, the varying response to diet and medications. As EoE shares some characteristics with both asthma and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 64 publications
1
36
0
Order By: Relevance
“…The clinical and endoscopic characteristics of EoE in PPI responders and nonresponders in our study are similar to those reported elsewhere [20][21][22][23][24]. This reinforces the recent consensus that considered EoE and PPI-REE as different diseases on the same spectrum that should be recognized as EoE [2,[23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 91%
“…The clinical and endoscopic characteristics of EoE in PPI responders and nonresponders in our study are similar to those reported elsewhere [20][21][22][23][24]. This reinforces the recent consensus that considered EoE and PPI-REE as different diseases on the same spectrum that should be recognized as EoE [2,[23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 91%
“…As proposed by Atkins et al, 16 understanding the extent of a patient's response to therapy could add information to their phenotype and disease severity. 16 In work by Shoda et al, 17 3 groups of EoE patients could be identified.…”
Section: Response To Therapymentioning
confidence: 99%
“…As proposed by Atkins et al, 16 understanding the extent of a patient's response to therapy could add information to their phenotype and disease severity. 16 In work by Shoda et al, 17 3 groups of EoE patients could be identified. 17,18 A mild form was identified that responded to all forms of treatment, including PPIs (these patients may have been defined as PPI-responsive esophageal eosinophilia or PPI-REE in the recent past).…”
Section: Response To Therapymentioning
confidence: 99%
“…In this article, Atkins et al. discuss potential paradigms for subtyping EoE using the lessons learned from asthma and inflammatory bowel disease. They propose different scenarios allowing for potential separation of mild, moderate, and severe phenotypes based on symptoms, histology, or molecular pathways.…”
Section: Is It Time For Phenotypes In Eosinophilic Oesophagitis?mentioning
confidence: 99%